PARENTING STRESS PADA IBU YANG MEMILIKI ANAK AUTIS - Nur Fitriyani Hardi; Ferra Puspito Sari (UIN Sunan Kalijaga Yogyakarta, 2019)
The presence of children in the family becomes happiness for parents, especially mothers. But this will be different when a family has child with autism that behavioral, social, and communication disorders. Raising an autistic child can certainly be stressful for a mother. A mother is stigmatized by the limitations of the child, the difficulty of talking to children will be easier because it requires additional help. This condition overcomes stress and emotion. The purpose of this study was to description of parenting stress mothers who have autistic child. This study uses qualitative research with phenomenological methods. The data collection technique uses the data triangulation method with phenomenological data analysis. The results of the study concluded that varied maternal stress arising from caring for autistic child. Physiological responses that easily tired, cognitive responses that feel embarrassed, disappointed, afraid, and sadness, and behavioral responses that crying, beating and pinching children. Keywords : autism, emotion, mothers, stress